Exploring the Organization and Framing of the Literature Review of English Language Education Study Program Theses - Erina Andriani (Journal of English Teaching, 2022)
Literature reviews provide the literature that illustrates the common knowledge and the researchers’ stand in their research. The literature review is designed with suitable organization and framing so the readers can build their knowledge. However, only few studies on the organization and framing of a literature review. Therefore, the researcher wanted to conduct a study on English Language Education Study Program (ELESP) theses. There are two research questions in this research: “How are the literature reviews of the ELESP students’ theses organized?” and “How are the literature reviews of the ELESP students’ theses framed?” The goal of this research is to explore the organization and framing of the literature review of the ELESP students’ theses. This research used content analysis. The data were gathered from thirty theses in education and linguistic fields from batch 2016 to 2018. The instruments to gather the data were two structured observation sheets for the organization and framing. The result shows that for the organization, thirty theses used thematic organization, none of them used chronological organization, and combinations of organization existed. Regarding the framing, some elements, author, year, topic, and result, were always mentioned in every observed thesis.